A study on the application of forensic science in criminal investigations in zone 1 of the Nigeria police - Sarki, Zakariyya Muhammad (2020)
Despite the rate of crimes that affects socio-economic development as well as the safety of individuals in Nigeria, the Nigeria Police (NP) appears to underutilize forensic science techniques in criminal investigations. Perceptual issues, personnel, motivational and organizational factors as well as the challenges affecting the general functions of the NP could be responsible for this situation. However, studies to specifically understand the reasons for the NP's inability to incorporate forensic science into their activities, even when forensic units and departments exist for years in the organisation, are few. This current study, therefore, explored issues related to the application of forensic science in criminal investigations by the NP. Its main objectives were to 1) profile the Investigating Police Officers (IPOs) in terms of sociodemographic markers and personality traits, 2) determine the availability of forensic science, 3) reasons for the (in)adequacy of forensic facilities, 4) determine the motivation and perception of forensics of the IPOs, and 5) identify the organisational culture and challenges faced in applying forensic science by the NP. The study was cross-sectional, utilizing a self-administered survey battery and semistructured interviews as instruments for data collection. The location of the study was zone 1 of the NP with IPOs as the respondents. Systematic sampling was used to select the 416 survey respondents, while purposive sampling was used in selecting the 12 interview participants. SPSS version 24 was used to analyze the data; descriptive and inferential statistics were generated using regression analysis, Mann Whitney test, Kruskal-Wallis test, and Pearson’s correlation, among others. Seven quantitative group hypotheses and four qualitative themes were formulated. Six null hypotheseswere rejected. The IPOs have an excellent perception of forensic science, and the perception was associated with motivation and personality traits. It was evidenced that there were inadequate forensic facilities that were related to organisational culture and motivation. The relationships among some challenges were identified: unreliable databases, lack of inter-agency cooperation, corruption and undue interference in investigations. From the themes formulated, the qualitative findings revealed that there were 1) positive prospects for the utilization of forensic science in criminal investigations by the NP, 2) essential rationales were expressed with regards to the inadequate utilization of forensic science, and 3) real challenges that should be addressed. The results herein suggest the need for more facilities, NP training, and updating of skills to improve investigation works.